Prevalence of the C282Y and H63D mutations in the HFE gene in patients with hereditary haemochromatosis and in control subjects from Northern Germany - NIELSEN, P. (2010)
Br J Haematol. 1998 Dec;103(3):842-5. Prevalence of the C282Y and H63D mutations in the HFE gene in patients with hereditary haemochromatosis and in control subjects from Northern Germany. Nielsen P, Carpinteiro S, Fischer R, Cabeda JM, Porto G, Gabbe EE. Abteilung für Medizinische Biochemie, Universitätskrankenhaus Eppendorf, Hamburg, Germany. Abstract Mutation analysis was performed for two HFE mutations (C282Y, H63D) in unrelated patients with hereditary haemochromatosis (n = 92), family members of patients (n = 34), and unrelated controls (n = 157) from Northern Germany, 87/92 patients (94.6%) revealed the C282Y mutation in homozygous form, five were heterozygous. No H63D mutation was found in 174 chromosomes of patients homozygous for C282Y, whereas four of the heterozygote patients also carried the H63D mutation. Among the control group, 9.6% were heterozygotes for C282Y. 2/157 subjects were homozygous, 37/157 were heterozygous for the H63D mutation, but showed no signs of iron overload. PMID: 9858243 [PubMed - indexed for MEDLINE]